STRATEGI PEMASARAN QOMESHOP BALOWERTI KOTA KEDIRI UNTUK MENINGKATKAN LOYALITAS PEMBELIAN DI MASA PANDEMI - Rahmadani, Hafizd Eka; Ernestivita, Gesty; Sasongko, M. Zuhdi (Universitas Nusantara PGRI Kediri, 2022)
The emergence of the Covid-19 pandemic has affected many business sectors, including the fashion business. With this difficult situation, business owners are required to be able to survive by implementing the right and right marketing strategies. An important part of the marketing strategy is the marketing mix, which consists of the 4Ps, namely Product, Price, Place and Promotion. With the implementation of the 4P marketing strategy, it is expected to increase purchase loyalty, which means customers remain loyal and make regular repeat purchases. This study aims to determine the implementation of the Qomeshop marketing strategy to increase purchase loyalty during the pandemic. This study uses a qualitative method with a descriptive approach. Data collection techniques are using triangulation techniques in the form of observations, interviews and documentation. Informants in the study are owners and buyers of Qomeshop products. From the results of the study, it was concluded that Qomeshop used a marketing strategy in the form of a 4P marketing mix to increase purchase loyalty during the pandemic.